Reducing error and improving efficiency during vascular interventional radiology: implementation of a preprocedural team rehearsal. - Morbi, A; Hamady, MS; Riga, C; Kashef, E; Pearch, B; Vincent, C; Moorthy, K; Vats, A; Cheshire, N; Bicknell, C (2012)
PURPOSE: To determine the type and frequency of errors during vascular interventional radiology (VIR) and design and implement an intervention to reduce error and improve efficiency in this setting. MATERIALS AND METHODS: Ethical guidance was sought from the Research Services Department at Imperial College London. Informed consent was not obtained. Field notes were recorded during 55 VIR procedures by a single observer. Two blinded assessors identified failures from field notes and categorized them into one or more errors by using a 22-part classification system. The potential to cause harm, disruption to procedural flow, and preventability of each failure was determined. A preprocedural team rehearsal (PPTR) was then designed and implemented to target frequent preventable potential failures. Thirty-three procedures were observed subsequently to determine the efficacy of the PPTR. Nonparametric statistical analysis was used to determine the effect of intervention on potential failure rates, potential to cause harm and procedural flow disruption scores (Mann-Whitney U test), and number of preventable failures (Fisher exact test). RESULTS: Before intervention, 1197 potential failures were recorded, of which 54.6% were preventable. A total of 2040 errors were deemed to have occurred to produce these failures. Planning error (19.7%), staff absence (16.2%), equipment unavailability (12.2%), communication error (11.2%), and lack of safety consciousness (6.1%) were the most frequent errors, accounting for 65.4% of the total. After intervention, 352 potential failures were recorded. Classification resulted in 477 errors. Preventable failures decreased from 54.6% to 27.3% (P < .001) with implementation of PPTR. Potential failure rates per hour decreased from 18.8 to 9.2 (P < .001), with no increase in potential to cause harm or procedural flow disruption per failure. CONCLUSION: Failures during VIR procedures are largely because of ineffective planning, communication error, and equipment difficulties, rather than a result of technical or patient-related issues. Many of these potential failures are preventable. A PPTR is an effective means of targeting frequent preventable failures, reducing procedural delays and improving patient safety.